Clinical-epidemiological behavior of tuberculosis-HIV coinfection at Simão Mendes National Hospital. Guinea-Bissau, 2024 - Herrera-Santiesteban , Doris de la Caridad; Hernández-Barroso , Candelario Manuel; Corbacho-Faulkner , Amanda Camila; Martínez-Quintana , Rainel; Suárez-Fariñas , Frank Reydel; Serrano-Rodríguez , Shelenys (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
Introduction: Tuberculosis (TB) and human immunodeficiency virus (HIV) coinfection represents a lethal synergy, especially in sub-Saharan Africa. In Guinea-Bissau, the burden of this coinfection is high, but few up-to-date studies characterize its clinical and epidemiological behavior. Objective: To clinically and epidemiologically characterize new cases of TB/HIV coinfection treated at the Simão Mendes National Hospital (HNSM) during January–December 2024. Methods: Observational, descriptive, cross-sectional, and quantitative study. Ninety-six patients diagnosed with TB and HIV who initiated anti-TB treatment at HNSM in 2024 were included. Data were obtained from medical records. Sociodemographic, clinical, microbiological, immunological, and therapeutic variables were analyzed using descriptive statistics. Results: The mean age was 31.7 years (SD ±8.2); The under-20 age group was the most affected (37.5%). Males predominated (52.1%), and most were from Bissau (91.7%). New TB cases represented 85.4%, and the pulmonary form accounted for 71.9%. Sputum smear microscopy was negative in 54.8% of registered patients. The mean CD4 count was 198.4 cells/mm³, with 48.4% having counts <200 cells/mm³. 86.5% had been on antiretroviral therapy (ART) for ≥5 years, and all received concomitant ART. The treatment success rate was 37.5%, and the discontinuation rate reached 17.7%. Conclusions: Young adults with advanced immunosuppression and a high frequency of negative sputum smear microscopy predominated. Treatment discontinuation was high. Strategies are needed to strengthen data recording, reduce dropout rates, and improve microbiological diagnosis.